Synthesis of new quinoline -2-one derivatives - I.Al-Bayati, Redha; R.Ahamad, Mohammed.; S.Ahamed, Luma (Iraqi Journal of Science, 2023)
Series of new derivatives of quinoline-2-one were synthesized ,m-cresol was chosen as the starting material which was reacted with ethyl acetoacetate in presence of conc.sulphuric acid to give 4,7-dimethyl coumarin (I) which treated with nitric acid in the presence of sulpharic acid afforded 4,7-dimethyl-6-nitrocumarin (II) and 4,7-dimethyl-8-nitrocumarin (III) and then the compound (II) was treated with hydrazine hydrate80% to give a new compound 1-amino-4,7-dimethyl-6-nitroquinoline-2(1H)-one (IV).The latter compound was used to synthesize differentcompounds via the reaction with aldehydic azo compounds (V-VII) by Schiff base reaction to prouduce compounds(VIII-X), these azo compounds were prepared by reaction of different aromatic amines with salicyladehyde. in the other hand the compound (IV) was converted to diazonium salt compound and coupling it with either salicyladehyde to produce compound (XI) or with ethyl acetoacetate to produce compound (XII).These synthesized compounds were characterized by the available physical and spectral methods UV-Visible, FTIR, 1H-NMR.and 13C-NMR spectra.